DEVELOPING FINE MOTOR USING DEMONSTRATION METHOD, ASSIGNMENT AND MOZAIC TECHNIQUE AL-AMIN MARTAPURA KINDERGARTEN - hikmah nurul; Sulistiyana Sulistiyana (E-CHIEF Journal, 2021)
The problem of this research is that there are not yet development of fine motor skills in sticking in the year 2020/2021 as many as 8 people out of 10 children with a percentage of 80% of the B3 group in Al-Amin Martapura Kindergarten, Banjar Regency. The reason is that online learning is not clear, the process of learning activities is not directly involved, and there are no other media that are more varied, only using Children's Worksheets. The solutions used are demonstration methods, assignment assignments and mosaic techniques. The purpose of this study was to describe the implementation and analyze the development of fine motor skills of attached children through combining demonstration methods, assigning assignments, and using mosaic techniques. This study consisted of 3 cycles using a qualitative approach of Class Action Research (CAR). The subjects of this study were children of the B3 group at Al-Amin Martapura Kindergarten, Banjar Regency. The result of the study showed that the teacher's activity with a score of 23 or very good criteria, 90% of children's activities obtained very active criteria, and the result of the achievement of fine motor development reached 90% in the Very Well Developed category. It was concluded that through a combination of demonstration methods and giving assignments, they could develop fine motor skills using the mosaic technique.Keywords: Fine Motor, Demonstration, Assignment, Mozaic